Laparoscopic pelvic adnexal surgery in Nobel Medical College - Chaudhary, Amar Nath; Baral, Gehanath; Shrestha, Prajmi; Bhanshakarya, Rakina (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To share early experience of gynaecological laparoscopic surgeries for adnexal masses in Nobel Medical College and Teaching Hospital (NMCTH). Methods: This is a observational descriptive study in the Department of Obstetrics and Gynaecology of Nobel Medical College, Biratnagar for one year in 2019-2020. All the patients undergoing laparoscopic pelvic surgeries for adnexal masses were analysed for indication, type of procedure, complications and histopathological diagnosis. Results: A total of 123 laparoscopic surgeries were performed. Preoperative diagnosis in most of the cases was adnexal mass followed by adnexal evaluation for subfertility. The common surgical procedure was cystectomy followed by salpingo-oophorectomy in 80% of cases. The most common histopathological diagnosis was mature cystic teratoma (42; 34%) followed by endometriosis (29; 23.8%) and cystadenoma (25; 20.3%). Conclusions: Adnexal evaluation and surgical treatment were performed with laparoscopy. The common pathologies were mature cystic teratoma, endometriosis and ovarian cystadenomas.